Makna Simbolis dan Filosofis Kuliner Tradisional pada Upacara Tradisi di Kudus - Sri Indrahti; Siti Maziyah; Alamsyah Alamsyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Kudus is an area rich in historical and cultural sites related to the spread of Islam. In several tombs of religious leaders in Kudus, there are still traditional ceremonies which are always complemented by various culinary traditions. What are the symbolic and philosophical meanings of each of the traditional culinary traditions in some ways related to the five prominent figures of Islam in Kudus? In writing this article the research begins with collecting data which includes the collection of primary and secondary sources such as literature, observation, participatory, in-depth interviews, and Focus Group Discussion (FGD) with informants from various elements. All data that has been collected through the various approaches above will then be classified, connected or accumulated between data from one another, linked between primary sources and library sources or secondary sources, as a form of interpretation and synthesized in order to obtain research results . The results of the study show that the symbolic and philosophical meanings of each culinary tradition in some traditional ceremonies relating to the characterization of Islamization in Kudus are closely related to the greatness of the figure itself. Based on the culinary tradition, it can be seen that the beliefs of the Kudus community still have a relationship with previous beliefs (pre-Islam).